TINGKAT PEMANFAATAN E-LEARNING MAHASISWA UNIVERSITAS TERBUKA - Siti Julaeha; Dewi Padmo (MAJALAH ILMIAH PEMBELAJARAN, 2007)
The study was aimed at getting information about the use of elearningby UT's students in their learning process. Specifically,the study was conducted in order to collect information aboutfactors that encouraged students to use Internet and the problemsthat students faced in using Internet in their learning process.The population of this study was UT's students who registeredcourses with flnline learning resourres. The sample was selectedby a purposive random sampling techuique with the criteria: UT'sstudents from four faculties and a fJOstwaduate school and coursesthat were registered by many students. Data collected weredescriptively analyzedThe results of the study showed that f'1ctors encouraging students touse Internet in their learning process are the flexibility of use oftime for learning, the multiuse of Internet: for learning and fordoing works; and the speed of getting information. Even though,the students faced problems in using Iniernet for their learningprocess, such as geographical condition, the bad connection ofInternet, financial problem, the leek of facility (the provision ofcomputer), the lack of given information about Internet, and thelack of skills in using Internet.